1997
DOI: 10.1002/(sici)1097-4636(19970615)35:4<451::aid-jbm5>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of nickel-titanium shape memory metal and its corrosion behavior in human cell cultures

Abstract: Nickel-titanium alloy (Nitinol) is a metallic biomaterial that has a unique thermal shape memory, superelasticity, and high damping properties. Nitinol is potentially very useful in orthopedic surgery, for example. At present, there are not enough confirmative biocompatibility data available on Nitinol. The aim of our study was to clarify the primary cytotoxicity and corrosion rate of Nitinol in human cell cultures. Comparisons were made with stainless steel (Stst), titanium (Ti), composite material (C), and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
110
1
2

Year Published

1998
1998
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(117 citation statements)
references
References 29 publications
4
110
1
2
Order By: Relevance
“…12 Based on previous studies reported by Jia et al and Ryhanen et al, NiTi and stainless-steel nickel ionic dissolution rates measured in our study can be expected to be under the cytotoxic or carcinogenic level. 13,32 The average nickel dietary intake is about 160-900 g/day, which is almost 1000-fold higher than the measured dissolution rates. 33 Nevertheless, 34 On the other hand, nickel released in soft tissue from a metallic implant is likely to be bound to blood plasma protein such as albumin, transported, and only gradually excreted in urine or processed metabolically.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…12 Based on previous studies reported by Jia et al and Ryhanen et al, NiTi and stainless-steel nickel ionic dissolution rates measured in our study can be expected to be under the cytotoxic or carcinogenic level. 13,32 The average nickel dietary intake is about 160-900 g/day, which is almost 1000-fold higher than the measured dissolution rates. 33 Nevertheless, 34 On the other hand, nickel released in soft tissue from a metallic implant is likely to be bound to blood plasma protein such as albumin, transported, and only gradually excreted in urine or processed metabolically.…”
Section: Discussionmentioning
confidence: 83%
“…[12][13][14] NiTi alloy derives its good corrosion behavior from a homogeneous oxide layermainly TiO 2 -which spontaneously covers the surface of NiTi alloy in presence of oxygen. This passive surface layer, similar to those observed on titanium-based alloys, enhances NiTi high stability in most corrosive environments.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the current quantitative analyses of metal corrosion toxicity or biocompatibility use a combination method of incubating cultured cells in metal-immersed media. [3][4][5][6][7][8] Alloy discs, 3 wires, 4 particulates 5 of test metals have been used in cell cultures to explore the dose-effect relationship. 4 The cell growth around pieces of metal in culture dishes was observed and compared with that in control cultures.…”
Section: Introductionmentioning
confidence: 99%
“…The release of oxides and metal ions could be detected in the first few days immediately after the stent implantation. 3 However, corrosive breakdown might take place any time, even several years after implantation. At the tissue contact interface, the released ions may be "burst-out" locally, accumulated, and then taken up by the adjacent cells.…”
Section: Introductionmentioning
confidence: 99%
“…1 Intimal hyperplasia is one of the major mechanisms responsible for poststenting restenosis, and is mainly caused by the proliferation of vascular smooth muscle cells. 1,2 But the effects of electrochemical corrosion of stent materials on the tissue response, especially on the growth of vascular smooth muscle cells, had not been well studied. The release of oxides and metal ions could be detected in the first few days immediately after the stent implantation.…”
Section: Introductionmentioning
confidence: 99%